Principles of the issues of condition in the juristic study of transactions among ibadhis - al-Harithy, Salim bin Said; Mat Jubri@Shamsuddin, Mustafa (IIUM Press, 2020)
The issues of conditions are of great importance in the formation of the contractual process between the parties to the contract, and therefore it is necessary to edit them carefully to prevent the contracts from any defect that may result in invalidation, and since contemporary studies are scarce in gathering ibadi views in the theory of condition, the research has used the analytical inductive approach. In order to reach the opinion of the Ibadi in the fundamentals of the issues of condition, the fundamentals of the books of jurisprudence read the books of jurisprudence in ibadi, and then analyzed their opinions, to the conclusion that ibadi differed in many issues of condition, such as the origin in the provision of conditions, and the effect of the conditions violated They also differed in the interpretation of the non-issue of two conditions in a contract, and differed in the branches of the issues of conditions such as the sale of the deposit and the condition of innocence of defects, as it was found that they agreed in return that not all the incorrect conditions invalidated the contract.